The planning profile and the organizational lifecycle of Brazilian companies (Revista de Administração, 2010)
This study aims to analyze the profile of Brazilian companies in terms of their structuring of the planning process, in relation to their organizational lifecycle stage. It focuses on understanding how the structured process of planning, including strategic planning, the budget and budgetary control is being used by Brazilian companies in various stages of the organizational lifecycle. This empirical study was based on a survey of a sample of 111 companies. The data treatment methods were confirmatory factor analysis with PLS-PM estimation and correlation. The reason for conducting the study was the observation that the development of a structured planning process, among other factors, depends on the stage at which the organization finds itself, which may help one to understand its management control change process. The study concludes that there is a correlation between organizational lifecycle stages and the formal planning profile among the companies surveyed. However, the lack of a budget at company startup, when this is not regarded as an enterprise priority, and when the firm is in decline, when it should be seen as a lever for recovery, induces reflections on the opportunities missed by those organizations that do not prioritize a structured planning process.